An overview of particulate matter measurement instruments - Amaral, Simone Simões [UNESP]; de Carvalho, João Andrade [UNESP]; Costa, Maria Angélica Martins [UNESP]; Pinheiro, Cleverson (MDPI, 2015)
This review article presents an overview of instruments available on the market for measurement of particulate matter. The main instruments and methods of measuring concentration (gravimetric, optical, and microbalance) and size distribution Scanning Mobility Particle Sizer (SMPS), Electrical Low Pressure Impactor (ELPI), and others were described and compared. The aim of this work was to help researchers choose the most suitable equipment to measure particulate matter. When choosing a measuring instrument, a researcher must clearly define the purpose of the study and determine whether it meets the main specifications of the equipment. ELPI and SMPS are the suitable devices for measuring fine particles; the ELPI works in real time. In health-related studies, a Diffusion Charger is the instrument that best characterizes the surface of ultrafine particles. Several methods and different particle measuring instruments should be used to confirm the values obtained during sampling.
Keywords: Measurement instruments; Particle matter emissions; Pollution; Sampling